Description of Mothers' Knowledge, Attitudes, and Behavior Regarding Deworming The Children Against Soil-Transmitted Helminthiasis at The Lampaseh Health Center in Banda Aceh City - Suryawati; Putra, Teuku Romi Imansyah; Liansyah, Tita Menawati; Maulina, Novi; Maulidina, Rizka Yuliani; Al-Muchtari, Teuku Az Zikri (Institute of Topical Disease Universitas Airlangga, 2024)
Helminth infections are a significant public health problem in developing countries, including Indonesia, where the prevalence ranges from 60% to 90%. One common helminth infection is Soil-Transmitted Helminthiasis (STH), which particularly affects children. One of risk factors is children who lack personal hygiene, especially when they are playing with soil. The increased incidence of STH can be prevented by deworming programs, and the role of parents, especially maternal parenting. This study aims to determine the description of the level of knowledge, attitudes and behavior of mothers on deworming the children against STH at the Lampaseh Health Center, Banda Aceh City, Indonesia. This research is descriptive with a cross-sectional design. The sample consists of mothers with children aged 2-12 years, selected using accidental sampling techniques. Data were collected through interviews using structured questionnaires. The results showed that the level of maternal knowledge of deworming the children against STH categorized as good (95.1%), quite good (3.9%), and less good (1.0%) as well as the attitude of mothers was categorized into good (51.5%), quite good (46.6%), and less good (1.9%). However, the mother’s behavior was good (69.9%) and less good (30.1%). The conclusion was that the knowledge, attitudes, and behavior of mothers on deworming the children against STH need to be maintained and improved.